Is the Equal Rights Amendment “Lost?”: A Contemporary Analysis of the ERA - Zarrella, Lila (Bellarmine Law Society Review, 2023)
In January of 2020, Virginia became the thirty-eight state to ratify the Equal Rights Amendment (ERA). A Constitutional amendment becomes law when three-quarters of the states––or thirty-eight out of fifty––ratify the amendment. To this day, the ERA remains in limbo and as of yet has not been added to the Constitution due to numerous controversies surrounding its ratification––principally, the deadline for ratification passed in 1982, and five states have rescinded their ratification of the ERA. This paper seeks to examine the current state of the ERA from an analysis of the ratification process as well as the best ways to achieve gender equality under the law. It seeks to explore whether the ERA is legally viable as well as if it is politically prudent.